Inhibiting RIPK1 Limits Neuroinflammation and Alleviates Postoperative Cognitive Impairments in D-Galactose-Induced Aged Mice - Duan, Shangchun; Wang, Xueqin; Chen, Gong; Quan, Chengxuan; Qu, Shuangquan; Tong, Jianbin (Frontiers in Behavioral Neuroscience, 2018)
Abstract Neuroinflammation plays a critical role in the pathogenesis of postoperative cognitive dysfunction (POCD) of the elderly patients. Receptor-interacting protein kinase1 (RIPK1) is a key molecular switch modulating inflammation, apoptosis and necroptosis. Here we investigated whether inhibiting RIPK1 by necrostatin-1 could limit neuroinflammation and attenuate POCD in D-Galactose-induced aged mice. The mice were subjected to anesthesia and partial hepatectomy, and necrostatin-1 was administered intraperitoneally 1 h prior to anesthesia and surgery. Cognitive function and movement were tested 24 h after surgery by open field, Barnes maze and puzzle box. The hippocampal tissues were collected to detect the following: neuroinflammation (Iba-1, IL-1α, IL-1β, TNF-α), Necroptosis (Propidium iodide labeling, RIPK1, NF-κB), and neuroplasticity (doublecortin, NR2B, GluA1, GluA2). We found that anesthesia and surgery induced a significant deficit in spatial memory acquisition and impairment of executive function and memory to simple task in D-Galactose-induced aged mice. Inhibiting RIPK1 by necrostatin-1 strikingly mitigated cognitive impairment and alleviated postoperative amplified neuroinflammation, necroptosis and GluA1 loss in hippocampus. These suggest that targeting RIPK1 by necrostatin-1 may serve as a promising therapeutics for prevention of POCD in elderly patients.